Artistas de Buenos Aires. (Mexico City : Museo de Arte Moderno, 1990)
Alvaro, Jorge ; Aro, Elizabeth ; Audivert, Eduardo ; Beccarini, Magdalena ; Benedit, Luis F. ; Bertani, Ernesto ; Bianchedi, Remo ; Burton, Mildred ; Carletti, Alicia ; Castilla, Américo ; Conte, Guillermo ; Dimirjián, Jorge ; Dobarro, Nora ; Dompé, Hernán ; Dowek, Diana ; Eckell, ana ; Fazzolari, Fernando ; Finocchietti, Maria ; Hoffmann, Eduardo ; Lecuona, Juan ; etc.
Artistas de Buenos Aires, Museo de Arte Moderno, Mexico D.F., Julio - Agosto de 1990
boek
Keywords: Buenos Aires